Atletas de Cristo no futuro e os sintomas de ansiedade - Vieira, Rosângela Ricardo (2011)
Think the theme of Christ athletes in football and anxiety symptoms from data collected on athletes from football clubs in two of the state of Pernambuco is the purview of this work. as a means of compreendr and analyze the power of belief and ritual in life, these athletes, to what extent this belief may int1uence the anxiety level of the athletes ahead of soccer matches. As the study of religious forms used by athletes through the ritual before the matches start. The methodological approach of our research is qualitative and descriptive. we used the method emperor and the data were collected from structured interviews. In the interviews, the athletes of Christ recognized the importance of religious faith in their lives as well as the effectiveness of belief and ritual in the soccer world. In the dynamics of football and religion are intertwined psyche as the mind of the athlete may be strongly int1uenced by faith and will directly providing new construction in the sporting context